Securing the West : Politics, Public Lands, and the Fate of the Old Republic, 1785-1850 - Van Atta, John Robert (Book collections on Project MUSE., 2014)
Few issues defined the period between American independence and the Mexican War more sharply than westward settlement and the role of the federal government in that expansion. In Securing the West, John R. Van Atta examines the visions of the founding generation and the increasing influence of ideological differences in the years after the peace of 1815. Americans expected the country to grow westward, but on the details of that growth they held strongly different opinions. What part should Congress play in this development? How much should public land cost? What of the families and businesses left behind, and how would society's institutions be established in the West? What of the premature settlers, the "squatters" who challenged the rule of law while epitomizing democratic daring? Taking a broad approach, Van Atta addresses three interrelated queries: First, how did competing economic beliefs and divergent cultural mandates influence the various outcomes of this broad debate over the means, timing, and purposes of settling the trans-Appalachian West? Second, what alternative visions of western society lay behind the battles among policy makers within the government and the interested parties who would sway them? Third, why did settlement of the West take such a different course in the end from that which the earliest leaders of the republic intended? This story explores dimensions of the federal lands question that other historians have minimized or left out entirely. Van Atta draws upon a range of sources known to have influenced the public discourse, including congressional debates, committee reports, and correspondence; editorial writings by the famous and unknown; and news coverage in various widely circulated newspapers and magazines of the period. Much of the attention focuses on Congress--the elected leaders who advocated divergent plans about western lands. In Congress, more than any other place, public leaders articulated basic concerns about the character, structure, direction, and destiny of society in the early United States. By 1830, many other important national concerns had become critically entangled with land disposition, creating points of ideological tension among rival regions, parties, and interests in the early years of the republic--particularly in Jacksonian America